Extracellular Nanovesicle Enhanced Gene Transfection Using Polyethyleneimine in HEK293T Cells and Zebrafish Embryos - Zhang, Zhenzhen; Wen, Kai; Zhang, Chao; Laroche, Fabrice; Wang, Zhenglong; Zhou, Qiang; Liu, Zunfeng; Abrahams, Jan Pieter; Zhou, Xiang (Frontiers in Bioengineering and Biotechnology, 2020)
It is a hot topic for improving efficiency and decreasing the toxicity of gene transfection reagents. The extracellular nanovesicles (EVs) that are released by cells play an important role in intercellular communication, and naturally designed for genetic exchange between cells. Here we show that the EVs have a large beneficial effect in polyethyleneimine (PEI)-mediated transfection of a GFP-encoding plasmid into HEK293T cells. An improvement as high as ~ 500%, as well as a decrease in toxicity, were observed in a specific concentration range of PEI. The EVs also greatly improved the transfection of the same plasmid into zebrafish embryos. The measured increase in transfection efficiency makes EV a promising candidate for enhancement of the quality of current PEI-based transfection technique.